Before and after a disease outbreak: Tracking a keystone species recovery from a mass mortality event. (April 2020) - Gizzi, Francesca; Jiménez, Jesús; Schäfer, Susanne; Castro, Nuno; Costa, Sónia; Lourenço, Silvia; José, Ricardo; Canning-Clode, João; Monteiro, João
Abstract: Mass mortality events involving marine taxa are increasing worldwide. The long-spined sea urchin Diadema africanum is considered a keystone herbivore species in the northeastern Atlantic due to its control over the abundance and distribution of algae. After a first registered mass mortality in 2009, another event off the coasts of Madeira archipelago affected this ecologically important species in summer 2018. This study documented the 2018 D. africanum mass mortality event, and the progress of its populations on the southern coast of Madeira island. A citizen science survey was designed targeting marine stakeholders to understand the extent and intensity of the event around the archipelago. Underwater surveys on population density prior, during and after the mass mortality, permitted an evaluation of the severity and magnitude of the event as well as urchin population recovery. A preliminary assessment of causative agents of the mortality was performed. The event was reported in the principal islands of the archipelago reducing the populations up to 90%. However, a fast recovery was registered during the following months, suggesting that the reproductive success was not compromised. Microbiological analyses in symptomatic and asymptomatic individuals, during and after the event, was not conclusive. Nevertheless, the bacteria Aeromonas salmonicida, or the gram-negative bacteria, or the interaction of different types of bacteria may be responsible for the disease outbreak. Further studies are needed to assess the role of pathogens in sea urchin mass mortalities and the compound effects that sea urchins have in local habitats and ecological functioning of coastal marine ecosystems. Highlights: Diadema africanum recovery after mass mortality hints high resilience to disease. Disease outbreaks may act as a mediator of a keystone species population control. Combining monitoring & citizen science paints a better picture of disease outbreaks.